Business model adaptation to the COVID-19 crisis: Strategic response of the Spanish cultural and creative firms - Montserrat Pe\~narroya-Farell; Francesc Miralles (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Surviving in a humanitarian disaster such as the COVID-19 pandemic is a big challenge for micro, small, and medium-sized enterprises in all industries. Furthermore, cultural and creative firms face additional challenges. Many of those firms have survived the effects of the pandemic by proposing redesigned business models that have brought new added value in response to environmental hostility; they have strategically responded to the crises by adapting their business model. According to the extant literature, in VUCA (volatile, uncertain, complex and ambiguous) environments, dynamic capabilities are developed to detect and seize new opportunities and reconfigure the company's assets. However, in very hostile environments, such as the COVID-19 crisis, the dynamic capabilities approach fails to explain the firm owners' strategic decisions. A cross-case comparative analysis of ten micro and small firms in Spain's cultural and creative industries has been conducted to examine how enterprises adapted to the COVID-19 crisis and the different organizational capabilities they implemented. This work proposes a new framework that postulates that business model adaptation is better understood under the emergency management theory and improvisational capability, instead of only under the dynamic capabilities lens. Organizational proximity in the diffusion of innovations under the open innovation paradigm is also critical to understanding the business model adaptation. From an academic perspective, this article enriches the current understanding of business model asdaptation by micro, small, and medium-sized enterprises in very hostile environments. The new framework intends to offer managers concrete guidelines about systematically adapting their business models in hostile situations.
Keywords: 650; business model adaptation; cultural industries; improvisation capability; open innovation; COVID-19